Relative paleointensity (RPI) in the latest Pleistocene (10–45 ka) and implications for deglacial atmospheric radiocarbon. (1st July 2018) - Channell, J.E.T.; Hodell, D.A.; Crowhurst, S.J.; Skinner, L.C.; Muscheler, R.
Abstract: We report magnetic properties and relative paleointensity (RPI) proxies from a suite of 10 conventional piston cores and Kasten cores from the SW Iberian Margin collected during cruise JC089 of the RSS James Cook in August 2013. Mean sedimentation rates are in the 10–20 cm/kyr range. Age models were acquired by correlation of Ca/Ti and Zr/Sr XRF core-scanning data to L* reflectance from the Cariaco Basin that is, in turn, tied to the Greenland ice-core chronology. The natural remanent magnetization (NRM) is represented by a single magnetization component carried by a low-coercivity mineral (magnetite), although reflectance and bulk magnetic properties indicate the presence of a high-coercivity (hematitic) magnetic phase, possibly from eolian dust. The presence of fine-grained hematite means that the sediments are not ideal for RPI studies, however the detrital hematite does not appear to contribute to the NRM or anhysteretic remanent magnetization (ARM). In order to test the usefulness of the RPI data, we construct a stack of 12 RPI records from the SW Iberian Margin for the 0–45 ka interval and compare it with a stack of 12 globally distributed marine and lake records, chosen on the basis of mean sedimentation rates (>15 cm/kyr) and superior age models. The two stacks are similar, but different from published RPI stacks, particularly for the 10–30 ka interval, and imply a virtual axial dipole moment (VADM) high at ∼15–18 ka followed by a drop in field strength from ∼15 to 13 ka. A revised VADM estimate calculated from Greenland 10 Be ice-core flux using a contemporary age model is remarkably consistent with the new overall RPI stack, based on Iberian Margin and global RPI records. The elevated atmospheric 14 C levels of the last ice age cannot, however, be fully explained by this RPI stack although relative changes such as the long-term drop in atmospheric 14 C from 30 to 15 ka are reproduced, supporting the hypothesis of a combined influence of production rate and ocean ventilation on 14 C during the last ice age. Highlights: Revised view of relative paleointensity for the latest Quaternary (0–45 ka). Stack of SW Iberian and global relative paleointensity records for 0–45 ka. RPI stack consistent with recalculated 10 Be-based estimate of field intensity. Implications for the carbon cycle, ocean ventilation, and the "mystery interval".